Oestrus synchronization in sheep using GnRH-PGF2alpha- GnRH protocol as compared to two injections of PGF 2alpha - KUMAR, SHIVA; SUNDARAVADANAN, V K (The Indian Journal of Animal Reproduction, 2023)
In group I (n = 15), the ewes were given 0.004mg of buserelin acetate (Receptal) on day ' 0 ' followed by 100mg ofcloprostenol on 7th day and a second injection of 0.004mg of buserelin acetate on exhibition of oestrus and 3 hours beforebreeding. In group II (n = 15), two injections of 100mg cloprostenol was given 11 days apart. The percentage of ewes exhibitingoestrus within 48 hours was significantly (p _::: 0.05) higher in group I and percentage of ewes exhibiting oestrus after 48 hours washigher in group II.Lowered plasma progesterone level was significant ( p _::: 0.05) in group I on the day of oestrus, although there was nosignificant difference in the oestradoil-1713 concentration between the two groups. Conception rate as determined by post-breedingplasma progesterone level and non-return rate in the two groups was 66 and 53 percent respectively.
Keywords: GnRH; PGF2alpha; oestrus synchronization